Rowing exercise increases cardiorespiratory fitness and brachial artery diameter but not traditional cardiometabolic risk factors in spinal cord-injured humans - Kopp Hansen, R.; Samani, A.; Laessoe, U.; Handberg, A.; Mellergaard, M.; Figlewski, K.; Thijssen, D. H. J.; Gliemann, L.; Larsen, R. G. (European Journal of Applied Physiology, 2023)
Purpose This study assessed the effects of upper-body rowing exercise on cardiorespiratory fitness, traditional cardiometabolic risk factors, and vascular health in individuals with spinal cord injury (SCI).